When Counterinsurgency Wins : Sri Lanka's Defeat of the Tamil Tigers - Hashim, Ahmed (Book collections on Project MUSE., 2013)
The tactics of the Tamil Tigers have been emulated by militant groups in Palestine, Iraq, Afghanistan, and Somalia. Whether or not the Sri Lankan counterinsurgency campaign can or should be emulated in kind, this book holds lessons for strategists and students of security and defense.--description provided by publisher.